Horror and the Posthuman: Edgar Allan Poe’s Narrative of Arthur Gordon Pym, Nonhumans, and Ethics - Hinds, Janie (Humanimalia, 2020)
“Horror and the Posthuman” offers a reading of The Narrative of Arthur Gordon Pym (1838) alongside a reading of critical animal studies that considers nonhumans as capable of not only being the object of ethical practice but also as the subject, as beings that initiate ethical encounters, thereby inhabiting and co-creating a moral world. The gothic extremes in Pym, often accompanied by animals produce an ethical point of view which creates, for both the title character and the reader, the nauseating unsettling of “the human” that accompanies horror. The nonhuman animal presence in this novel works, further, to unsettle the foundational expectations of narrative, thus providing a model for the decentering of the human and the humanism subtending its era.